Viabilidade econômica de três miniusinas para produção de biodiesel utilizando como matéria prima o óleo de crambe (Crambe Abyssinica Hochst) - Vernini, Adolfo Alexandre [UNESP] (2014)
This paper aimed at performing a study to identify, through economic indicators, the best settings for thr ee different production models of biodiese l miniplants, producing 44, 66 e 110 L. h - 1 . The study used cost rates of Cramble oil ( Crambe abyssinica Hochst ) as feddstock for biodiesel production. Methodology showed facilities description as well as determinin g and quantifying costs and incomes. Finally, economical viability analysis was carried out using the method of Net Present Value (NPV), return internal rate ( T IR) and payback discounted . After economic indicator analysis it was observed the viability for 66 and 110 L. h - 1 biodiesel miniplants implantation